Causal associations between psoriasis and atopic dermatitis: A bidirectional Mendelian randomization study - Zixia Wang; Hao Nie; Xinyu Fan; Muyao Wang; Weili Chen; Quncai Huang; Junchao Xiao; Wenhui Wang (PLoS ONE, 2025)
Background Although previous studies suggested associations between psoriasis and atopic dermatitis (AD), the directionality and causality of these relationships remain controversial. This study employed bidirectional Mendelian randomization to investigate the potential causal relationships between these two inflammatory skin conditions. Methods Genome-wide association statistics were obtained for psoriasis and AD from large-scale consortia and meta-analyses of genome-wide association studies. Inverse-variance weighting, as the primary analysis, was combined with five complementary sensitivity analyses to evaluate the robustness and potential pleiotropy of the data. Additionally, we performed gene mapping of psoriasis-associated single-nucleotide polymorphisms and subsequent pathway analysis to further elucidate the potential relationships. Results Genetic predisposition to psoriasis was significantly associated with a decreased risk of AD (odds ratio = 0.876; 95% confidence interval = 0.834–0.921; p = 1.6 × 10−7). Conversely, genetic predisposition to AD did not affect the risk of psoriasis. The associations remained consistent across multiple sensitivity analyses, and no evidence of horizontal pleiotropy was observed. Gene mapping identified eight key genes (ENSG00000249738, ENSG00000291336, ENSG00000291338, ENSG00000285703, OR2W1-AS1, HLA-DQA1, FBXL18, and nitric oxide synthase 2 (NOS2) located on chromosomes 5, 6, 7 and 17. Notably, NOS2 emerged as a core gene involved in key biological processes, including the TCR signaling pathway and protein metabolism. Conclusions This comprehensive MR study provided evidence of the protective causal effect of psoriasis on the risk of AD, whereas no reverse causal relationship was noted. These findings enhanced our understanding of the relationship between psoriasis and Ad and identified potential implications for their clinical management.